Curcumin in Reduction Size of Myoma Uteri - Akarapon Sukonthanonta; Paweena Phaliwong; Sinart Prommas (The Royal Thai College of Obstetricians and Gynaecologists, 2015)
Objective:The objectives of the study were to determine effects of curcumin in decreasing size of leiomyoma and to determine adverse effects of curcumin. Materials and Methods: The study was a prospective study conducted in reproductive women with leiomyoma in Bhumibol Adulyadej Hospital. 35 women with 81 leiomyoma lumps were recruited to participate by convenience sampling. Ultrasound measurement size of leiomyoma was done before treatment with curcumin. Patients were taken curcumin 1,200 milligrams orally per day for 6 months. Ultrasound measurement size of leiomyoma was repeated at 3 and 6 months after curcumin was started. Main outcomes measure was size of leiomyoma. Size of leiomyoma were compared between before and after taken curcumin for 6 months.Results: The mean diameter of leiomyoma was statistically different at before and after 3 (4.74 ± 2.78 centimeters VS 4.64 ± 2.75 centimeters) and 6 months (4.74 ± 2.78 centimeters VS 4.46 ± 2.61 centimeters) curcumin intake. And both mean volume of leiomyoma was statistically different at before and after 3 and 6 months curcumin intake. Adverse effect of curcumin was not found. Conclusions: Curcumin decreased size of myoma uteri after taken 6 months with statistically significant.